1977
DOI: 10.1111/j.1432-1033.1977.tb11927.x
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of Model Membranes from Phospholipid and Outer Membrane Proteins of Proteus mirabilis

Abstract: Outer membrane proteins extracted from isolated cell walls of Proteus mirabilis were able to combine with cell wall phospholipids in a model membrane system. The presence of outer membrane proteins in vesicular model membranes mediated the release of previously entrapped [14C]sucrose while [3H]inulin was retained. Incorporation of lipopolysaccharide from the same cell walls was not required for the formation of such selectively permeable membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

1979
1979
1991
1991

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 23 publications
1
35
0
Order By: Relevance
“…Several procedures were compared for the efficient and reproducible isolation of purified cell walls. The first procedure, a modification of one described by Nixdorff et al (1977), was used for the routine isolation of cell walls from P . syringue.…”
Section: Methodsmentioning
confidence: 99%
“…Several procedures were compared for the efficient and reproducible isolation of purified cell walls. The first procedure, a modification of one described by Nixdorff et al (1977), was used for the routine isolation of cell walls from P . syringue.…”
Section: Methodsmentioning
confidence: 99%
“…Nixdorff et al (22) reported that two major outer membrane proteins of Proteus mirabilis with apparent molecular weights of 36,000 and 39,000 formed hydrophilic pores in reconstituted membranes, and they claimed that the two kinds of pores have functionally similar properties, although the 39K protein preparation was assumed to contain a large amount of the 36K protein. Proteus mirabilis N-51, studied here, produces two major outer membrane proteins, i.e., 40K and 41K, and these two proteins may correspond to the 36K and 39K proteins, respectively, reported by Nixdorff et al (22). However, Proteus mirabilis N-51C1 lacking the 40K porin showed low permeation of hydrophilic cephalosporins, and the diffusion rate of the drugs through the outer membrane was independent of the hydrophilic property of the solute (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This passive permeability is dependent to a large extent on a class of major outer membrane proteins [16,17] called matrix proteins [26], protein 1, protein I [11,30], or porins [16] The porins have been isolated from the outer membrane of Escherichia coli, Salmonella typhimurium, and Proteus mirabilis. They were shown to form permeability channels in vesicles reconstituted from phospholipids and lipopolysaccharide [16,17,23]. It was suggested that the active unit of porin aggregates is a trimer in E. coli and S. typhimurium [35,36].…”
Section: Summary the Three Types Of Porin (Matrix-proteins)mentioning
confidence: 99%